Using Molecular and Biological Tools for Assessment of TYLCV Resistant Tomato Cultivars Commercially Grown in Southern Palestine - Sahar Amro; Raed Alkowni; Abdul-Jalil Hamdan (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Tomato, considered one of most important and popular crop, was infected by Tomato Yellow Leaf Curl Virus (TYLCV) which causes significant yields loss. Biological and molecular tools were used to evaluate the TYLCV incidence on tomatoes grown under commercial conditions. A total number of 72 tomato plants from each eight different tomato cultivars commercially planted in Palestine were tested for their virus infection which occurred naturally. The virus incidence was reported biologically based on visual inspections for the disease symptoms and molecularly by PCR tests, in two growing season periods: Summer (2006) and spring (2007). As a result, no cultivars were found “immune” to virus infection. However, fundamental differences in symptoms development and severity had been discovered. This study, which was carried out for the first time in Palestine, showed that some cultivars such as “3060” could be targeted as promising virus-tolerant ones. The sensitivity of molecular methods over bioassays was evaluated, and combined methods were suggested for any cultivars resistance assessments. Besides, research results revealed that the experimental conditions in Spring were not in favor of the virus spread, as the main virus vector (Bemisia tabaci) population number would be lower in the Summer season; thus the Spring season is seen as the best one for farmers to escape from TYLCV infections.